3-Bromo-4,5-Dihydroxybenzaldehyde Protects Against Myocardial Ischemia and Reperfusion Injury Through the Akt-PGC1α-Sirt3 Pathway - Qin, Shu-Guang; Tian, Hong-Yan; Wei, Jin; Han, Zhen-Hua; Zhang, Ming-Juan; Hao, Guang-Hua; Liu, Xin; Pan, Long-Fei (Frontiers in Pharmacology, 2018)
Natural marine products are useful candidates for the treatment of oxidative and inflammatory diseases, including myocardial ischemia. 3-bromo-4,5 -dihydroxybenzaldehyde (BDB), a natural bromophenol isolated from marine red algae, has been shown to display anti-microbial, anti-oxidative, anti-cancer, anti-inflammatory, and free radical scavenging activities. In this study, the potential protective effects of BDB against myocardial ischemia and reperfusion (IR) injury was investigated in an in vitro model mimicked by oxygen and glucose deprivation (OGD) in cardiomyocytes and in an in vivo model induced by coronary artery ligation in rats. The results showed that BDB attenuated the OGD-induced cytotoxicity in a dose-dependent manner, with no toxic effect when treated alone. BDB significantly decreased apoptosis and the cleavage of caspase-3 after OGD. We found that OGD-induced oxidative stress, as evidenced by increases of reactive oxygen species (ROS) and lipid peroxidation, as well as mitochondrial dysfunction, as measured by mitochondrial reporter gene, cytochrome c release and ATP synthesis, were markedly attenuated by BDB treatment. In addition, BDB increased the enzymatic activities of mitochondrial antioxidant enzymes, including IDH2, GSH-Px and SOD2. Western blot analysis showed that BDB increased Akt phosphorylation and upregulated the expression of Sirt3 and PGC1α after OGD. Furthermore, BDB-induced protection in cardiomyocytes was partially reversed by the Akt inhibitor and downregulation of PGC1α. BDB also attenuated myocardial contractile dysfunction and activated the Akt-PGC1α-Sirt3 pathway in vivo. All these data suggest that BDB protects against myocardial IR injury through activating the Akt-PGC1α-Sirt3 pathway.